Key Parameters for Enhancing Diffraction Efficiency in Polarized Phase Holograms - Stephen Maina Njoroge (Science and Technology: Developments and Applications Vol. 6, 2025)
Holography has a wide application in medicine, optical computers, and scanners among others. Conventional studies on analogue holograms have mainly been conducted on image generation, processing and reconstruction. However, these conditions may vary thus affecting hologram quality. In phase-based holograms, where amplitude information is disregarded, the quality of the holographic image is compromised. Since convection holography uses photosensitive recording interference patterns in holographic material, there is a need to evaluate aberration or how high intensity of light has been reconstructed. In this chapter, a discussion on the fundamental parameters of holograms such as exposure time and processing chemical composition effect in phase holograms are presented. The recording of the holograms was carried out in a darkroom. The experiment involved the introduction of a polarizing beam splitter (PBS) on the reference beam path. This was done to generate the s-polarized and polarized beams. The power of the emerging s- and p-polarized beams from the reference beam was measured. Using the set-up plane wave transmission holograms were recorded as the commercial half-wave plate was rotated at angles of 0.0°, 22.5°, 45.0°, 67.5°, and 90.0°. It is worth noting that the optimization of these parameters can result in obtaining a phase hologram image of approximately 16% diffraction efficiency at an exposure time of 20s. Moreover, by investigating the influence of objective beam polarization hologram image quality can be controlled further. Finally, by varying the polarization orientation, diffraction efficiency and fringe visibility are greatly affected. As a result, it is possible to achieve a Polarized phase hologram of diffraction efficiency of approximately 21.1%.